2023
DOI: 10.1007/s40620-023-01586-z
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian hemodialysis patients' willingness to receive the COVID-19 vaccine booster dose: a multicenter survey

Abstract: Background Health authorities have struggled to increase vaccination uptake since the COVID-19 vaccines became available. However, there have been increasing concerns about declining immunity after the initial COVID-19 vaccination with the emergence of new variants. Booster doses were implemented as a complementary policy to increase protection against COVID-19. Egyptian hemodialysis (HD) patients have shown a high rate of hesitancy to COVID-19 primary vaccination, yet their willingness to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Egyptian researchers surveyed reasons for denying boosters for COVID-19 in hemodialysis patients. They found that more than one-half of the patients did not want to receive boosters, and booster hesitancy was associated with female sex, younger age, single marital status, Alexandria and urban residency, and the use of a tunneled dialysis catheter [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Egyptian researchers surveyed reasons for denying boosters for COVID-19 in hemodialysis patients. They found that more than one-half of the patients did not want to receive boosters, and booster hesitancy was associated with female sex, younger age, single marital status, Alexandria and urban residency, and the use of a tunneled dialysis catheter [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings support the use of COVID-19 vaccinations to improve SARS-CoV-2 outcomes of patients undergoing chronic dialysis (14). SARS-CoV-2 booster dose hesitancy among MHD patients is a major concern and emphasizes the need to develop effective strategies to increase vaccine compliance (12).…”
Section: Yavuz Et Al Reported That Approximately 495% Of Patients On ...mentioning
confidence: 56%
“…In addition, our study showed a mortality rate of 12.1% among unvaccinated patients. Hemodialysis patients have a high rate of hesitancy regarding COVID-19 primary vaccination (12). A previous study revealed lower mortality rates in fully and partially vaccinated individuals (5.3% and 8.3%, respectively) (13).…”
Section: Yavuz Et Al Reported That Approximately 495% Of Patients On ...mentioning
confidence: 98%